2010
DOI: 10.1111/j.1439-0418.2009.01489.x
|View full text |Cite
|
Sign up to set email alerts
|

Flight and crawling activities of Diabrotica virgifera virgifera (Coleoptera: Chrysomelidae) in relation to morphometric traits

Abstract: Morphometric traits and body weight are often used to study changes in fitness. For the invasive alien maize pest, Diabrotica virgifera virgifera LeConte, little information is available regarding the possible relationship between morphometric traits and adult activity, which reflects the ability to disperse and invade. Flight and crawling activities of D. v. virgifera adults were investigated in relation to six different morphometric traits as well as body weight, sex and age. This laboratory study revealed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
22
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(24 citation statements)
references
References 66 publications
2
22
0
Order By: Relevance
“…Although dispersal was not directly investigated in this study, we have provided morphological results (i.e., larger hind wings in females versus males) similar to that of Li et al (2009) andLi et al (2010) that are supportive of increased female D. v. virgifera longdistance dispersal capabilities, based on longer and broader elytra and now hind wings compared with males. We hypothesize that the observed sexual dimorphism in wing shape may be related to the sexspeciÞc dispersal behavior of D. v. virgifera and that newly mated females play a key role in the dispersal process and are likely to promote population establishment, as they likely form the leading edge of the invasion front.…”
Section: August 2013supporting
confidence: 62%
See 3 more Smart Citations
“…Although dispersal was not directly investigated in this study, we have provided morphological results (i.e., larger hind wings in females versus males) similar to that of Li et al (2009) andLi et al (2010) that are supportive of increased female D. v. virgifera longdistance dispersal capabilities, based on longer and broader elytra and now hind wings compared with males. We hypothesize that the observed sexual dimorphism in wing shape may be related to the sexspeciÞc dispersal behavior of D. v. virgifera and that newly mated females play a key role in the dispersal process and are likely to promote population establishment, as they likely form the leading edge of the invasion front.…”
Section: August 2013supporting
confidence: 62%
“…They showed that elytra width and length were inßuenced by sex and that elytron width and length were signiÞcantly broader in females than in males, regardless of age. Li et al (2010) found that ßight activity was greatest in young adults, especially preovipositional but mated females, with females having signiÞcantly longer and broader elytra and implicated in the continued range expansion of this pest in Europe and the United States. Previously, Mabry et al (2004) found a similar result and showed that female elytra length was greater in rotation-resistant than susceptible individuals.…”
mentioning
confidence: 98%
See 2 more Smart Citations
“…Sixteen phenotypic traits were assessed according to Li et al (2009Li et al ( , 2010: five fitness traits (fecundity, overwintering egg survival, larva-to-adult survival, egg-to-adult survival, and adult lifespan), four activity traits (proportion of adults crawling, crawling speed, proportion of adults flying, and flight take-off response), and seven morphometric traits of adults (fresh body weight, elytra length and width, pronotum length and width, head capsule width, and hind tibia length). Assessments were conducted with D. v. virgifera from two rearing series (= repetitions) of each colony (Begley, 2013).…”
Section: Assessing Phenotypic Traitsmentioning
confidence: 99%